Psychologia myślenia - Twardowski, Kazimierz (Filozofia Nauki, 1993)
The text, first published here in virue of the survived original typescript, contains an outline of the sersies of lectures delivered by the founder of Lvov-Warsaw School in 1908 at John Casimir University. The notions like „thinking”, „presentation”, „memory”, „association” are objects of his minute inquiry.